Deskripsi Motivasi Siswa untuk Mengikuti Konseling Teman Sebaya Di SMA Negeri 1 Sungayang - Syaputra, Yogi Damai; Monalisa, Monalisa (Jurnal Bimbingan dan Konseling Terapan, 2018)
Adolescence is a time of self-discovery, one of the efforts made to achieve the identity of teenagers can be pursued with the achievement of a mature relationship with peers. Teenagers spend more time with their peers. Peer execution is very urgent in determining attitudes and behavior, as teenagers strive to be free from family and not dependent on their parents, so that any problems they face will be more likely to share the problem with their peers. Peer counseling is an activity of mutual care and interpersonal mutual assistance among fellow students that take place in everyday life, using active listening skills and problem-solving skills in equal position among peers. In SMA 1 Sungayang some students have attended peer counseling, one time, twice or even four times in peer counseling. This study aims to reveal the level of student motivation in following peer counseling. This research uses quantitative descriptive method, with 76 research sample students. Data obtained through questionnaire, then continued with interpretation of data or process of interpreting data. The results of this study revealed that the motivation of students to follow peer counseling activities belong to the high category.